Estimated Breeding Values of Beef Sires Can Predict Performance of Beef-Cross-Dairy Progeny - Martín, Natalia; Coleman, Lucy; López-Villalobos, Nicolás; Schreurs, Nicola; Morris, Stephen; Blair, Hugh; McDade, Julie; Back, Penny; Hickson, Rebecca (Frontiers in Genetics, 2021)
On average, half of the animal’s estimated breeding value (EBV) is passed on to their progeny. However, it is not known how the performance of beef-cross-dairy cattle relates to the EBV of their beef sire. Such information is required to determine the genetic potential of beef sires selected based on existing EBV to be used on dairy cows in New Zealand. This study evaluated the relationship between the EBV of 30 Angus and 34 Hereford sires, and the performance of their progeny for birth, growth and carcass traits, via progeny testing of 975 beef-cross-dairy offspring born to dairy cows and grown on hill country pasture. Overall, BREEDPLAN EBV did predict progeny performance of the beef-cross-dairy cattle from this study. Gestation length and birth weight increased with increasing sire EBV (mean 0.37-0.62 days and 0.52-0.64 kg respectively, P<0.05). Age at weaning decreased with increasing sire EBV for live weight at 200d (0.17-0.21 days per extra kilo of sire EBV, P<0.05) but sire EBV for live weight at 200d had no effect on the live weight of the progeny at 200d for either breed (P>0.05). Live weight increased with sire EBV for live weight at 400, 600 and 800 days of age, by a similar amount for both breeds (between 0.23-0.42 kg increase in progeny live weight per extra kilo of sire EBV, P<0.05). The relationships were more inconsistent for carcass traits. For Hereford, carcass weight and eye muscle area increased with increasing sire EBV (0.27 kg and 0.70 cm2 respectively, P<0.05). For Angus, marble score increased by 0.10 with 1% extra in sire EBV for intramuscular fat (P<0.05). Rib fat depth tended to increase with sire EBV for both breeds (P<0.1). EBV derived from beef-breed data work in dairy-beef systems but maybe slightly less than the expected 0.5 units of performance per unit of EBV. New Zealand farmers should consider BREEDPLAN EBV when selecting sires to mate dairy cows or when buying beef-cross-dairy calves for beef production, to ensure the resulting calves are born safely and on time, and then grow well to produce carcasses of suitable meat and fat composition.